Internacionalización monetaria y bancaria - Ávila, Jorge C. (2005)
The paper combines a brief review of basic monetary theory, a discussion of the critical monetary and banking experience undergone by Argentina between 1980 and 2002, an essay on the stability of velocity of circulation and a proposal for reform. Our thesis is that after a hyperinflation episode (or under currency substitution), when velocity of circulation stops being a parameter to become a very volatile magnitude, an independent or active monetary policy (a floating exchange-rate regime) becomes a high-risk policy. After reviewing some proposals for monetary and banking reform by well-known international economists, all of them doing without a national central bank, we advance the proposal to substitute a reserve currency (dollar, euro) for the national currency, and an offshore banking system that works under the jurisdiction of the issuers of reserve currencies for the present onshore banking system. The whole point is to import from the "islands of stability of the world" basic economic institutions with very high reversion costs to provide the country with the widest possible stability horizon.